A "carrier-load" perspective method for investigating regional water resource carrying capacity. (1st October 2020) - Liao, Xia; Ren, Yitian; Shen, Liyin; Shu, Tianheng; He, Hongman; Wang, Jinhuan
Abstract: Many regions globally have been facing the challenges of water scarcity and water pollution along with the rampant urbanization process. These challenges highlight the urgency to investigate appropriately the regional water resource carrying capacity (RWRCC) which is a metric for examining and guiding sustainable regional development. Although existing studies have devoted efforts on RWRCC research, the definition of RWRCC and its evaluation method remain arguable. Given this background, this paper introduces a "carrier-load" perspective method for investigating RWRCC. In developing this method, RWRCC performance is determined jointly by two components, namely, carrier and load of regional water resources system. The two components are comprehended and identified through examining the regional water cycling system. A measurement model for RWRCC is established by investigating the interaction between carrier and load. The effectiveness of the "carrier-load" method on RWRCC is demonstrated by conducting an empirical study to 31 provinces of China. The results reveal that the RWRCC performances vary significantly between different regions as they are subject to different performances of carrier and load. The proposed "carrier-load" method provides a theoretical reference for conducting RWRCC research. The evaluation results by applying the method can facilitate decision-makers to formulate tailor-made policy instruments at regional level to ensure the capabilities of water resources are not overloaded or less-utilized in achieving their sustainable development mission. Highlights: Giving a carrier-load Concept of regional water resources carrying capacity (RWRCC). Identifying watercarrier and load through examining regional water cycling system. Developing the measurement of RWRCC based on a"carrier-load" perspective. Conducting a China case for the established RWRCC measurement.